Drivers of range shifts in female wild eastern chimpanzees, Pan troglodytes schweinfurthii, following female death events - Abigail R. McClain; Steffen Foerster; Joseph T. Feldblum; Kara K. Walker; Deus Mjungu; Anne E. Pusey; Carson M. Murray (Animal Behaviour, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

A revised Proterozoic tectono-stratigraphy of the South Nicholson region, Northern Territory, Australia—insights from SHRIMP U–Pb detrital zircon geochronology - C. J. Carson; N. Kositcin; J. R. Anderson; P. A. Henson (Australian Journal of Earth Sciences, 2026)

Colorectal Cancer in the American Indian and Alaska Native Community: A Holistic Review - Angela R. Monetathchi; William O. Carson; Byron Upshaw; Autumn Lester; Emma Cleary; Alyssa Little; Felina M. Cordova-Marks; Jennifer Erdrich (Journal of Cancer Education, 2026)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

The discovery and preclinical pharmacology of JNJ-10450232 (NTM-006), a centrally penetrant, non-opioid structural analog of acetaminophen with comparable analgesic and anti-pyretic properties but no evidence of hepatotoxicity - Christopher M. Flores; John R. Carson; Ellen E. Codd; Scott L. Dax; Edwin K. Kuffner; Paul L. Stahle; Robert A. Neff; Gary E. Eichenbaum (Regulatory Toxicology and Pharmacology, 2025)

Evaluation of SARS-CoV-2 antibody detection methods for wild Cervidae - Joshua Hewitt; Grete Wilson-Henjum; Jeffrey C. Chandler; Aaron T. Phillips; Diego G. Diel; W. David Walter; Alec Baker; Jennifer Høy-Petersen; Guillaume Bastille-Rousseau; Tadao Kishimoto; George Wittemyer; Jeremy Alder; et al. (Preventive Veterinary Medicine, 2025)

Impact of sarcopenia and obesity on skeletal muscle size, gene expression, and mitochondrial function - Hector G. Paez; Christopher R. Pitzer; Jessica L. Halle; Peter J. Ferrandi; James A. Carson; Junaith S. Mohamed; Stephen E. Alway (GeroScience, 2025)
Skeletal muscle is a primary tissue of dysfunction during both aging and obesity. Recently, the coincidence of obesity and aging has gained attention due to the intersection of the obesity epidemic with an aging demographic. Both aging and obesity are associated with marked defects in skeletal muscle metabolic health. Despite these findings, we have a poor understanding of how obesity and aging may interact to impact skeletal muscle mass and metabolic health. Therefore, we investigated the impact of high-fat diet (HFD)-induced obesity on skeletal muscle mass, mitochondrial function, transcriptomics, and whole-body metabolism in young and aged mice. We observed main effects of diet and age on several measures of whole-body metabolic function (VO 2 , VCO 2 , and RER). Complex I-driven mitochondrial proton leak was significantly elevated by HFD-induced obesity across both age groups; however, a main effect of aging for reduced complex I leak was detected in the soleus muscle. Interestingly, aged animals fed a HFD did not exhibit lower muscle mass than chow-fed young animals, but did present with stark increases in muscle triglyceride content and a unique transcriptional response to HFD. HFD-induced obesity impacted the muscle transcriptome differently in the muscles of young and aged mice, indicating that obesity can change altered gene expression with age. Our findings suggest that the presence of obesity can both compound and counteract age-associated changes to muscle mass, gene expression, and mitochondrial function.

Functional brain network correlates of cardiorespiratory fitness and moderation by depression symptoms - Lauren R. Borrell; Andrew C. Venezia; J. Carson Smith (Brain Structure and Function, 2025)
Cardiorespiratory fitness may protect against or alleviate depression through neuroplastic mechanisms within disrupted brain networks underlying cognitive and affective symptoms. There is a scarcity of research examining the effects of cardiorespiratory fitness on functional brain networks in representative samples spanning adulthood. Further, little is known about the interaction of cardiorespiratory fitness with depression in these networks. To address this problem, this study made use of the NKI-Rockland sample dataset and magnetic resonance imaging to examine whether functional brain network features associated with cardiorespiratory fitness were moderated by depression symptom severity in a community sample of 217 participants (134 females, 83 males) between the ages of 18 and 71 ( M = 43.8 years, SD = 16.2). Cardiorespiratory fitness was positively associated with whole-brain modularity, between-network connectivity of the central executive and salience networks, and within-network connectivity of the default mode, central executive, and salience networks. The association of cardiorespiratory fitness and default mode network connectivity was stronger in the presence of moderate-to-severe depression symptoms. Taken together, these observations lend support to prior work that has demonstrated the associations of cardiorespiratory fitness with reduced concurrent and prospective depression risk and symptom severity. Depression symptoms moderated default mode network connectivity, suggesting that cardiorespiratory fitness may differentially impact neural substrates for those with moderate-to-severe depression symptoms.

A global survey for dust devil vortices on mars using MRO context camera images enabled by neural networks - Susan J. Conway; Valentin T. Bickel; Lori K. Fenton; Manish R. Patel; Helen C. Carson; Antoine Blouin; Justin Crevier; Evan Blanc; Bao Nhi Nguyen; James A. Holmes; Brian Jackson; Lonneke Roelofs (Planetary and Space Science, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Electronic cigarettes alter cardiac rhythm and heart rate variability hyperacutely in mice - Jocelyn A. Castellanos; Carson G. Cornett; David H. Gonzalez; Liqiao Li; Karla Luna; Holly R. Middlekauff; Rajat Gupta; Maria C. Jordan; Dennis Rünger; Yifang Zhu; Xuesi M. Shao; Kenneth P. Roos; et al. (Toxicology and Applied Pharmacology, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Limited effects of thinning on laminated root rot induced tree mortality in Douglas-fir forests of the Pacific Northwest, USA - Shawn B. McMurtrey; David N. Showalter; Adam R. Carson; Michael McWilliams; (Irene) Blakey Lockman; Everett M. Hansen; Jared M. LeBoldus (Forest Ecology and Management, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Invasive shrubs differentially alter autumnal activity for three common small‐mammal species - Brian Connolly; Chad R. Zirbel; Carson Keller; Mark Fuka; John L. Orrock (Ecology, 2024)
Seasonal variation in animal activity influences fitness and the intensity of ecological interactions (e.g., competition, predation), yet aspects of global change in the Anthropocene may catalyze shifts in seasonal activity. Invasive plants are components of global change and can modify animal daily activity, but their influence on animal seasonal activity is less understood. We examined how invasive woody shrubs (Autumn olive [ Elaeagnus umbellata ] and Amur honeysuckle [ Lonicera maackii ]) affect seasonal activity of three common small‐mammal species by coupling experimental shrub removal with autumnal camera trapping for two consecutive years at six paired forest sites (total 12 plots). Eastern chipmunks ( Tamias striatus ) foraged more, and foraging was observed at least 20 days longer, in shrub‐invaded forests. White‐footed mice ( Peromyscus leucopus ) foraged more in invaded than cleared plots in one study year, but P. leucopus autumn activity timing did not differ between shrub‐removal treatments. Fox squirrel ( Sciurus niger ) activity displayed year‐specific responses to shrub removal suggesting intraannual cues (e.g., temperature) structure S. niger autumnal activity. Our work highlights how plant invasions can have species‐specific effects on seasonal animal activity, may modify the timing of physiological processes (e.g., torpor), and could generate variation in animal‐mediated interactions such as seed dispersal or granivory.

NEOMOD 3: The debiased size distribution of Near Earth Objects - David Nesvorný; David Vokrouhlický; Frank Shelly; Rogerio Deienno; William F. Bottke; Carson Fuls; Robert Jedicke; Shantanu Naidu; Steven R. Chesley; Paul W. Chodas; Davide Farnocchia; Marco Delbo (Icarus, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Biophysical effects of an old tundra fire in the Brooks Range Foothills of Northern Alaska, U.S.A - Eric A. Miller; Carson A. Baughman; Benjamin M. Jones; Randi R. Jandt (Polar Science, 2024)

Global Patterns of Metal and Other Element Enrichment in Bog and Fen Peatlands - Chetwynd Osborne; Spencer Gilbert-Parkes; Graeme Spiers; Louis James Lamit; Erik A. Lilleskov; Nathan Basiliko; Shaun Watmough; Roxanne Andersen; Rebekka E. Artz; Brian W. Benscoter; Luca Bragazza; Suzanna L. Bräuer; et al. (Archives of Environmental Contamination and Toxicology, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Truffles in the sky: The impact of stochastic and deterministic drivers on Rhizopogon communities of the Madrean sky island archipelago - Carolina Piña Páez; Adam R. Carson; Daniel L. Luoma; Joseph W. Spatafora (Fungal Ecology, 2023)

Acardius acephalus in an aborted lamb - A. Morey Matamalas; F. Ridout; J. Dubuc; C. Bianco; R. Reichel; A. Carson (Journal of Comparative Pathology, 2023)

The case for stand management guidelines as dynamic as global change: Aspen forest stockings of the western Great Lakes - Michael T. Carson; John M. Zobel; Dustin R. Bronson; Amanda M. McGraw; Christopher W. Woodall; Christel C. Kern (Forest Ecology and Management, 2023)

Serotonin transporter availability in physically aggressive personality disordered patients: associations with trait and state aggression, and response to fluoxetine - Daniel R. Rosell; Mark Slifstein; Judy Thompson; Xiaoyan Xu; M. Mercedes Perez-Rodriguez; Margaret M. McClure; Erin A. Hazlett; Antonia S. New; Nabeel Nabulsi; Yiyun Huang; Richard E. Carson; Larry S. Siever; et al. (Psychopharmacology, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Natural Intertidal Oyster Reef Growth Across Two Landscape Settings and Tidal Ranges - Molly C. Bost; Antonio B. Rodriguez; Justin T. Ridge; Carson B. Miller; Stephen R. Fegley (Estuaries and Coasts, 2021)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Interlimb transfer and generalisation of learning in the context of persistent failure to accomplish a visuomotor task - D. A. E. Bolton; A. R. Buick; T. J. Carroll; R. G. Carson (Experimental Brain Research, 2019)

Consumption explains intraspecific variation in nutrient recycling stoichiometry in a desert fish - Eric K. Moody; Evan W. Carson; Jessica R. Corman; Hector Espinosa‐Pérez; Jorge Ramos; John L. Sabo; James J. Elser (Ecology, 2018)
Consumer‐driven nutrient recycling can have substantial effects on primary production and patterns of nutrient limitation in aquatic ecosystems by altering the rates as well as the relative supplies of the key nutrients nitrogen (N) and phosphorus (P). While variation in nutrient recycling stoichiometry has been well‐studied among species, the mechanisms that explain intraspecific variation in recycling N:P are not well‐understood. We examined the relative importance of potential drivers of variation in nutrient recycling by the fish Gambusia marshi among aquatic habitats in the Cuatro Ciénegas basin of Coahuila, Mexico. There, G. marshi inhabits warm thermal springs with high predation pressure as well as cooler, surface runoff‐fed systems with low predation pressure. We hypothesized that variation in food consumption among these habitats would drive intraspecific differences in excretion rates and N:P ratios. Stoichiometric models predicted that temperature alone should not cause substantial variation in excretion N:P, but that further reducing consumption rates should substantially increase excretion N:P. We performed temperature and diet ration manipulation experiments in the laboratory and found strong support for model predictions. We then tested these predictions in the field by measuring nutrient recycling rates and ratios as well as body stoichiometry of fish from nine sites that vary in temperature and predation pressure. Fish from warm, high‐predation sites excreted nutrients at a lower N:P ratio than fish from cool, low‐predation sites, consistent with the hypothesis that reduced consumption under reduced predation pressure had stronger consequences for P retention and excretion among populations than did variation in body stoichiometry. These results highlight the utility of stoichiometric models for predicting variation in consumer‐driven nutrient recycling within a phenotypically variable species.

Dietary lipophilic iron accelerates regional brain iron-load in C57BL6 mice - Douglas G. Peters; Carson J. Purnell; Michael P. Haaf; Qing X. Yang; James R. Connor; Mark D. Meadowcroft (Brain Structure and Function, 2018)

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

Aflatoxin contamination in corn sold for wildlife feed in texas - Nicholas R. Dunham; Steven T. Peper; Carson D. Downing; Ronald J. Kendall (Ecotoxicology, 2017)

Reduced white matter MRI transverse relaxation rate in cognitively normal H63D-HFE human carriers and H67D-HFE mice - Mark D. Meadowcroft; Jianli Wang; Carson J. Purnell; Douglas G. Peters; Paul J. Eslinger; Elizabeth B. Neely; David J. Gill; Megha Vasavada; Fatima Ali-Rahmani; Qing X. Yang; James R. Connor (Brain Imaging and Behavior, 2016)

Preferential binding to dopamine D3 over D2 receptors by cariprazine in patients with schizophrenia using PET with the D3/D2 receptor ligand [11C]-(+)-PHNO - Ragy R. Girgis; Mark Slifstein; Deepak D’Souza; Yih Lee; Antonia Periclou; Parviz Ghahramani; István Laszlovszky; Suresh Durgam; Nika Adham; Nabeel Nabulsi; Yiyun Huang; Richard E. Carson; et al. (Psychopharmacology, 2016)
Rationale Second-generation antipsychotics occupy dopamine D 2 receptors and act as antagonists or partial agonists at these receptors. While these drugs alleviate positive symptoms in patients with schizophrenia, they are less effective for treating cognitive deficits and negative symptoms. Dopamine D 3 receptors are highly expressed in areas of the brain thought to play a role in the regulation of motivation and reward-related behavior. Consequently, the dopamine D 3 receptor has become a target for treating negative symptoms in combination with D 2 antagonism to treat positive symptoms in patients with schizophrenia. Objective The purpose of this study was to determine the cariprazine receptor occupancies in brain for D 2 and D 3 receptors in patients with schizophrenia. Methods Using [ 11 C]-(+)-PHNO as a radioligand, positron emission tomography (PET) scans were performed in eight patients at baseline and postdose on days 1, 4, and 15. Plasma and cerebrospinal fluid (CSF) samples were analyzed for cariprazine concentrations. Results A monotonic dose-occupancy relationship was observed for both receptor types. After 2 weeks of treatment, near complete (∼100 %) occupancies were observed for both receptors at a dose of 12 mg/day. At the lowest cariprazine dose (1 mg/day), mean D 3 and D 2 receptor occupancies were 76 and 45 %, respectively, suggesting selectivity for D 3 over D 2 receptors at low doses. An exposure-response analysis found a ∼3-fold difference in EC 50 (D 3 = 3.84 nM and D 2 = 13.03 nM) in plasma after 2 weeks of dosing. Conclusion This PET imaging study in patients with schizophrenia demonstrated that cariprazine is a D 3 -preferring dual D 3 /D 2 receptor partial agonist.

Coastal sea level changes, observed and projected during the 20th and 21st century - M. Carson; A. Köhl; D. Stammer; A. B. A. Slangen; C. A. Katsman; R. S. W. van de Wal; J. Church; N. White (Climatic Change, 2016)

Erratum to: Development of polymorphic microsatellite markers for the microendemic pupfishes Cyprinodon julimes and C. pachycephalus - Evan W. Carson; Rochelle R. Beasley; Kenneth L. Jones; Stacey L. Lance; Ma de Lourdes Lozano-Vilano; Lilia Vela-Valladares; Iris Banda-Villanueva; Thomas F. Turner; Mauricio De la Maza-Benignos (Conservation Genetics Resources, 2015)

Maternal Behavior and Physiological Stress Levels in Wild Chimpanzees (Pan troglodytes schweinfurthii) - Margaret A. Stanton; Matthew R. Heintz; Elizabeth V. Lonsdorf; Rachel M. Santymire; Iddi Lipende; Carson M. Murray (International Journal of Primatology, 2015)

Projecting twenty-first century regional sea-level changes - A. B. A. Slangen; M. Carson; C. A. Katsman; R. S. W. van de Wal; A. Köhl; L. L. A. Vermeersen; D. Stammer (Climatic Change, 2014)

Development of polymorphic microsatellite markers for the microendemic pupfishes Cyprinodon julimes and C. pachycephalus - Evan W. Carson; Rochelle R. Beasley; Kenneth L. Jones; Stacey L. Lance; Ma de Lourdes Lozano-Vilano; Lilia Vela-Valladares; Iris Banda-Villanueva; Thomas F. Turner; Mauricio De la Maza-Benignos (Conservation Genetics Resources, 2013)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Population structure in Chilean hake Merluccius gayi as revealed by mitochondrial DNA sequences - R. R. Vidal; E. W. Carson; J. R. Gold (Journal of Fish Biology, 2012)
Genetic variation and divergence among samples of Chilean hake Merluccius gayi , from three localities off the coast of Chile and one locality off the coast of northern Peru, were assessed using sequences from the control region of mitochondrial DNA. Homogeneity tests revealed occurrence of at least three distinct genetic stocks of M. gayi within the region sampled. Factors potentially contributing to genetic divergence among M. gayi probably include hydrodynamics and behaviour.

Real-time error detection but not error correction drives automatic visuomotor adaptation - Mark R. Hinder; Stephan Riek; James R. Tresilian; Aymar de Rugy; Richard G. Carson (Experimental Brain Research, 2010)

Microsatellite markers for species of the genus Dionda (Cyprinidae) from the American southwest - Mark A. Renshaw; Evan W. Carson; Ashley H. Hanna; Caird E. Rexroad; Trevor J. Krabbenhoft; John R. Gold (Conservation Genetics, 2009)

Automatic identification and truncation of boundary outlets in complex imaging-derived biomedical geometries - Xiangmin Jiao; Daniel R. Einstein; Vladimir Dyedov; James P. Carson (Medical & Biological Engineering & Computing, 2009)

Effect of extracellular products of Tenacibaculum maritimum in Atlantic salmon, Salmo salar L. - R Van Gelderen; J Carson; B Nowak (Journal of Fish Diseases, 2009)

What signs and symptoms would be expected after ingestion of this plant? - Samuel J. Stellpflug; Carson R. Harris (Journal of Medical Toxicology, 2009)

BACE1 Polymorphisms Do Not Influence Platelet Membrane β-secretase Activity or Genetic Susceptibility for Alzheimer’s Disease in the Northern Irish Population - S. Todd; A. J. McKnight; W. W. Liu; R. Carson; S. Heggarty; B. McGuinness; G. B. Irvine; D. Craig; A. P. Passmore; J. A. Johnston (NeuroMolecular Medicine, 2008)

The efficacy of colour cues in facilitating adaptation to opposing visuomotor rotations - Mark R. Hinder; Daniel G. Woolley; James R. Tresilian; Stephan Riek; Richard G. Carson (Experimental Brain Research, 2008)

The interference effects of non-rotated versus counter-rotated trials in visuomotor adaptation - Mark R. Hinder; Laura Walk; Daniel G. Woolley; Stephan Riek; Richard G. Carson (Experimental Brain Research, 2007)

Dual adaptation to two opposing visuomotor rotations when each is associated with different regions of workspace - Daniel G. Woolley; James R. Tresilian; Richard G. Carson; Stephan Riek (Experimental Brain Research, 2007)

NeuroAIDS, Drug Abuse, and Inflammation: Building Collaborative Research Activities - Joan W. Berman; Monica J. Carson; Linda Chang; Brian M. Cox; Howard S. Fox; R. Gilberto Gonzalez; Glen R. Hanson; Kurt F. Hauser; Wen-Zhe Ho; Jau-Shyong Hong; Eugene O. Major; William F. Maragos; et al. (Journal of Neuroimmune Pharmacology, 2006)

Spatiotemporal distribution of heparan sulfate epitopes during murine cartilage growth plate development - Ronald R. Gomes; Toin H. Kuppevelt; Mary C. Farach-Carson; Daniel D. Carson (Histochemistry and Cell Biology, 2006)

Neuromuscular-skeletal constraints on the acquisition of skill in a discrete torque production task - Jonathan Shemmell; Matthew Forner; Benjamin Tathem; James R. Tresilian; Stephan Riek; Benjamin K. Barry; Richard G. Carson (Experimental Brain Research, 2006)

Visual feedback alters the variations in corticospinal excitability that arise from rhythmic movements of the opposite limb - R. G. Carson; T. N. Welsh; M- Pamblanco-Valero (Experimental Brain Research, 2005)

Governing coordination: behavioural principles and neural correlates - R. G. Carson; J. A. S. Kelso (Experimental Brain Research, 2004)

Bimanual aiming and overt attention: one law for two hands - S. Riek; J. R. Tresilian; M. Mon-Williams; V. L. Coppard; R. G. Carson (Experimental Brain Research, 2003)

Switching patients to aripiprazole from other antipsychotic agents: a multicenter randomized study - Daniel E. Casey; William H. Carson; Anutosh R. Saha; Amy Liebeskind; Mirza W. Ali; Darlene Jody; Gary G. Ingenito (Psychopharmacology, 2003)

Wild fish are not a significant reservoir for Neoparamoeba pemaquidensis (Page, 1987) - G M Douglas‐Helders; D R Dawson; J Carson; B F Nowak (Journal of Fish Diseases, 2002)
Amoebic gill disease (AGD), caused by the protozoan Neoparamoeba pemaquidensis (Page, 1987) is the most important disease affecting salmon farms in Tasmania. Reservoirs for this protozoan parasite are largely unknown. This study investigated wild fish as a potential reservoir of N. pemaquidensis . A total of 325 wild fish, comprising 12 different fish species, were caught from and around salmon farms and examined for the presence of AGD. None of the wild fish were infected with AGD. In a laboratory trial, seahorse, Hippocampus abdominalis , greenback flounder, Rhombosolea tapirina, and Atlantic salmon, Salmo salar, were challenged with N. pemaquidensis . Neoparamoeba pemaquidensis was detected on the gills on 10 of 15 (66.7%) flounder, nine of 24 (37.5%) seahorses, and six of six (100%) Atlantic salmon. However, paramoebae positive flounder and seahorse lacked the characteristic AGD gill pathology. It is concluded that AGD does not appear in wild fish and wild fish do not seem to be a reservoir of the pathogen.

Role of peripheral afference during acquisition of a complex coordination task - R. G. Carson; C. J. Smethurst; M. Forner; D. P. Meichenbaum; D. C. Mackey (Experimental Brain Research, 2002)

Neural compensation for compliant loads during rhythmic movement - Mackey D.; Meichenbaum D.; Shemmell J.; Riek S.; Carson R. (Experimental Brain Research, 2002)

A Spiking Neuron Model for Binocular Rivalry - Carlo R. Laing; Carson C. Chow (Journal of Computational Neuroscience, 2002)

Turning On and Off with Excitation: The Role of Spike-Timing Asynchrony and Synchrony in Sustained Neural Activity - Boris S. Gutkin; Carlo R. Laing; Carol. L. Colby; Carson C. Chow; G. Bard Ermentrout (Journal of Computational Neuroscience, 2001)

The effect of obstacle position on reach-to-grasp movements - Vanessa L. Coppard; James R. Tresilian; Mark Mon-Williams; Richard G. Carson (Experimental Brain Research, 2001)

Alleviation of aluminum toxicity to Rhizobium leguminosarum bv. viciae by the hydroxamate siderophore vicibactin - Nicola J. Rogers; Kerry C. Carson; Andrew R. Glenn; Michael J. Dilworth; Martin N. Hughes; Robert K. Poole (BioMetals, 2001)

Orthostatic intolerance and the postural tachycardia syndrome: genetic and environment pathophysiologies - David Robertson; John R. Shannon; Italo Biaggioni; Andrew C. Ertl; André Diedrich; Robert Carson; Raffaello Furlan; Giris Jacob; Jens Jordan; and Team (Pflügers Archiv - European Journal of Physiology, 2000)

Evidence for polynuclear iron(III) clusters in the root nodule bacterium, Rhizobium leguminosarum bv. viciae WSM710 - Timothy G. St. Pierre; Kerry C. Carson; John Webb; Andrew R. Glenn; Michael J. Dilworth (BioMetals, 1999)

Activation of the skeletal α-actin promoter during muscle regeneration - Daniel R. Marsh; James A. Carson; Lynn N. Stewart; Frank W. Booth (Journal of Muscle Research and Cell Motility, 1998)

The influence of joint position on the dynamics of perception-action coupling - R. G. Carson; Stephan Riek (Experimental Brain Research, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Specificity of siderophore-mediated transport of iron in rhizobia - K. C. Carson; A. R. Glenn; M. J. Dilworth (Archives of Microbiology, 1994)

Specificity of siderophore-mediated transport of iron in rhizobia - K. C. Carson; A. R. Glenn; M. J. Dilworth (Archives of Microbiology, 1994)

Siderophore and organic acid production in root nodule bacteria - K. C. Carson; S. Holliday; A. R. Glenn; M. J. Dilworth (Archives of Microbiology, 1992)